2015
DOI: 10.5194/bgd-12-13483-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protist communities in a marine oxygen minimum zone off Costa Rica by 454 pyrosequencing

Abstract: <p><strong>Abstract.</strong> Marine planktonic protists, including microalgae and protistan grazers, are an important contributor to global primary production and carbon and mineral cycles, however, little is known about their population shifts along the oxic-anoxic gradient in the water column. We used 454 pyrosequencing of the 18S rRNA gene and gene transcripts to study the community composition of whole and active protists throughout a water column in the Costa Rica Dome, where a stable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 34 publications
5
23
0
Order By: Relevance
“…Yet, protist distributions in OMZ are largely unknown. Our results indicated that the alpha diversity found in OMZ in the Pacific Ocean is similar to that of epipelagic waters, as observed by Jing et al (2015), indicating a relatively high diversity in hypoxic waters. The most 400 abundant groups in the OMZ retrieved with the rRNA were Chrysophyceae, Ciliates and Dinoflagellates.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Yet, protist distributions in OMZ are largely unknown. Our results indicated that the alpha diversity found in OMZ in the Pacific Ocean is similar to that of epipelagic waters, as observed by Jing et al (2015), indicating a relatively high diversity in hypoxic waters. The most 400 abundant groups in the OMZ retrieved with the rRNA were Chrysophyceae, Ciliates and Dinoflagellates.…”
supporting
confidence: 82%
“…The most 400 abundant groups in the OMZ retrieved with the rRNA were Chrysophyceae, Ciliates and Dinoflagellates. The presence of Chrysopyceae in the OMZ has been reported before (Jing et al 2015), together with that of anaerobic Ciliates (e.g. mesodiniids) and Dinoflagellates (Orsi et al 2012, Parris et al 2014, Wylezich et al 2018.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Furthermore, in regions like the eastern tropical Pacific Ocean and the tropical Indian Ocean, the mesopelagic zone contains layers with very low oxygen concentration, known as oxygen minimum zones (OMZs), which play a key role in the nitrogen cycle and contain specific microbial communities [16]. However, protist communities in OMZ or anoxic basins have received less attention than those in oxygenated mesopelagic waters [17][18][19][20] and changes in protist relative activity in the DSL or OMZ at the global scale remain unknown.…”
Section: Introductionmentioning
confidence: 99%